Characterization of interlaminar shear properties of nanostructured unidirectional composites. Issue 2 (1st February 2021) - Gomes, M. C. C. B.; Cardoso, L. D. R.; Damm, D. D.; Silva, F. S. Da; Corat, E. J.; Trava-Airoldi, V. J.
ABSTRACT: Composites are key materials in the aerospace and aeronautics industry. However, a disadvantage is their susceptibility to interlaminar fracture because of poor adhesion at fiber surface and matrix interface. Carbon nanotube (CNT) growth onto carbon fiber (CF) surface is a promising method to increase CF–matrix adhesion. This work studies interlaminar properties of unidirectional CF composites and thermoset matrix, with CNT deposition on CF surface. CNT growth goes along in chemical vapor deposition with a floating catalyst of ferrocene and flow of CO2 and C2 H2 precursors. Tensile strength tests on single-filament and CF tow showed the preservation of tensile properties after preparation and growth. Results of the interlaminar shear strength study presented a 35% increase in shear strength and a 15% increase in fracture toughness at the initial delamination crack. An overall analysis reveals an improvement in the interlaminar interface on mechanical tests; however, fracture toughness analysis is limited by fragile pathways in intralaminar regions.